2016
DOI: 10.1177/1440783315593181
|View full text |Cite
|
Sign up to set email alerts
|

Gender patterns in domestic labour among young adults in different living arrangements in Australia

Abstract: Most research on gender divisions of housework focuses on couple and family households. This article extends this literature to examine gender differences in domestic labour across living arrangements, with particular focus on young adults. Using time-diary data from the nationally representative Australian Bureau of Statistics (ABS) Time Use Survey (2006) it examines the amount and composition of domestic work performed by 20–34-year-olds ( n = 889) living with parents, in a share household, alone, or in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…If women are more likely than men to take responsibility for household-related tasks, for example, they may then potentially spend more time in their neighbourhood as a result. 20 21 If more affluent neighbourhoods tend to promote lower BMI, as many, though not all, commentators suggest, 12 then the duration of exposure could play a role in explaining gender differences in the socioeconomic patterning of overweight and obesity. Furthermore, women in some contexts may also tend to be involved more often in activities that take place in the local area, such as schools and community groups.…”
Section: Discussionmentioning
confidence: 99%
“…If women are more likely than men to take responsibility for household-related tasks, for example, they may then potentially spend more time in their neighbourhood as a result. 20 21 If more affluent neighbourhoods tend to promote lower BMI, as many, though not all, commentators suggest, 12 then the duration of exposure could play a role in explaining gender differences in the socioeconomic patterning of overweight and obesity. Furthermore, women in some contexts may also tend to be involved more often in activities that take place in the local area, such as schools and community groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gardening and home maintenance are considered to be non-routine housework as they need not be performed as often and can be flexibly arranged over the week. Grocery shopping is considered to be routine as well as "gender-neutral" (Baxter, 2002;Craig, Powell, and Brown, 2015;Kan and He, 2018).…”
Section: Types Of Domestic Workmentioning
confidence: 99%
“…Whereas Etheridge and Spantig ( 2020 ) found that controlling for time spent on housework and childcare reduced the gender gap in well‐being, Adams‐Prassl et al ( 2020 ) found it did not. Although gender disparities in domestic responsibilities typically increase upon the birth of the first child (Baxter et al, 2008 ), childcare is not solely responsible for gender differences in family responsibilities—large and significant gender differences in household labor exist among couples without children as well (e.g., Craig et al, 2016 ). The present research explores this question among financial advisors by asking male and female financial advisors the extent to which family or other responsibilities outside the workplace has been a stressor for them since the onset of COVID‐19.…”
Section: Related Literaturementioning
confidence: 99%